Learning Arabic in Ashwat Science (Khalil Bin Ahmad Perspective) - Okitra Asri Nurazim; Tulus Musthofa (Jurusan Pendidikan Bahasa Arab, 2024)
In learning Arabic, Al-Ashwat plays an important role in understanding a language. There is a lot of literature that states that studying and studying al-Ashwat must take precedence before studying and studying other components and skills of language. There are several Arab figures or scientists who study the science of ashwat, but in this study the author only focuses on the figure of ashwat, namely Khalil bun Ahmad. The purpose of this study is to find out the role, contribution, and thoughts of Khalil bin Ahmad in the science of ashwat in Arabic language learning. And to know the development of Arabic sciences in the hands of al-Khalil bin Ahmad al-Farahidi. This research is included in the type of qualitative research using library research methods. The source of data from this study is the book 'Ilmu al-Aswad al-'Arabiyyah by Muhammad Jawad An-Nuuri, articles, journals, papers, theses, and encyclopedias. Data collection techniques in this study by a) collecting literature related to Khalil bin Ahmad's thoughts in ashwat, b) classifying books, documents, or other sources, c) quoting Khalil bin Ahmad's views according to the context of the research focus, and d) grouping data according to research systematics. And the results of this study are: That Khalil bin Ahmad's role in the science of ashwat was to introduce the use of dots and harakat, he also marked the sound of dhammah with a small waw letter above the letter, the sound of fathah with alif written horizontally, and the sound of kasrah with a lowercase ya' that connects under the letter. And as for the contribution and development of Arabic language sciences in the hands of khalil bin Ahmad in the science of ashwat including in pioneering the formulation of Nahwu and Sharf rules.